Comparative study of safety and efficacy of labetalol and nifedipine in the management of hypertensive disorders of pregnancy: A prospective observational study - Syed Sujat Pasha; Shifa Roohi (Al Ameen Journal of Medical Sciences, 2025)
Background: Hypertensive disorders of pregnancy is a leading cause of maternal and fetal morbidity and mortality. Antihypertensive agents such as labetalol and nifedipine are commonly used, but comparative data on their effectiveness and safety are still being evaluated. Objectives: To compare the efficacy and safety of labetalol and nifedipine in the management of hypertensive disorders in pregnancy. Methods: This prospective observational study included 120 pregnant women with hypertensive disorders of pregnancy divided into two groups: group A (n=60) received oral labetalol, and group B (n=60) received oral nifedipine. Blood pressure, maternal outcomes, and fetal outcomes were monitored over 7 days and until delivery. Results: Both drugs significantly reduced systolic and diastolic blood pressure. labetalol showed slightly faster control (mean BP normalization in 3.2 days vs 3.6 days for nifedipine,p<0.05). Maternal side effects were minimal and similar in both groups. Fetal outcomes (birth weight, Apgar scores, NICU admissions) were comparable. Conclusion: Both labetalol and nifedipine are effective and safe in managing hypertensive disorders of pregnancy. Labetalol provides slightly faster control of blood pressure with comparable maternal-fetal outcomes.